Paradoxical preexcitation during cryoablation of a concealed parahisian accessory pathway. Issue 10 (27th August 2018) - Akerström, Finn; Puchol, Alberto; Pachón, Marta; Martín‐Sierra, Cristina; Rodíguez‐Padial, Luis; Arias, Miguel A.
Abstract: A 16‐year‐old male presented with an orthodromic atrioventricular reentrant tachycardia over a concealed parahisian accessory pathway (AP). Cryoablation of the AP resulted in transient manifestation of a fully preexcited sinus rhythm of parahisian AP morphology. Potential causes for the paradoxical preexcitation include inadvertent atrioventricular nodal block, sourse‐sink mismatch, as well as the activation of a dormant AP capable of anterograde conduction.